Effect of viewership and information on materialism and compulsive buying behavior- A comparative study of television and digital advertising - Ahmad, Farah; Mahfooz, Yasser (Archives of Business Research, 2020)
This comparative study between television and digital advertising explores the effect of viewership and information on compulsive buying behavior. To test the relationships in proposed framework, data was collected through self-administered questionnaires using convenience sampling technique. Out of 285 responses, 267 were chosen for the purpose of study and analyzed for descriptive statistics as well as relationship between information, materialism and buying behavior. Significant positive relationship was found between all dimensions. For both online and television advertising, viewership factors were found to have a higher impact than information on materialism. On compulsive buying behavior, viewership was more effective as compared to information, whereas for television advertising information had a greater effect.